Population dynamics of Variola albimarginata Baissac, 1953 and Variola louti Fabricius, 1775 (Perciformes: Serranidae) in Sulawesi Sea, Indonesia - DEWI SHINTA ACHMAD; MUH. SALEH NURDIN; APRIS ARA TILOME; ABIGAIL M. MOORE (Biodiversitas Journal of Biological Diversity, 2024)
Abstract. Achmad DS, Nurdin MS, Tilome AA, Moore AM. 2024. Population dynamics of Variola albimarginata Baissac, 1953 and Variola louti Fabricius, 1775 (Perciformes: Serranidae) in Sulawesi Sea, Indonesia. Biodiversitas 25: 978-989. The lyretail groupers Variola louti Fabricius, 1775 and Variola albimarginata Baissac, 1953 (Epinephelinae) are valuable foodfishes. IUCN Red List assessments classified both species as Least Concern, while noting that some stocks are overfished. The purpose of this study on the population dynamics of Variola groupers in Kwandang Bay was to evaluate the exploitation level for both species in this important grouper fishing area of the Sulawesi Sea, Indonesia. Population dynamics parameters were calculated based on length-frequency data collected from October 2022 to September 2023 using the ELEFAN I response surface analysis option in FISAT II. The asymptotic length at infinity TL? was 54.90 cm for V. louti and 54.40 cm for V. albimarginata with von Bertalanffy growth function K values 0.54 and 0.55, respectively. Recruitment occurred throughout the year, with monthly percentages of 1.08-13.52 % and 1.61-14.99%, respectively. Natural and fishing mortality were M = 1.04/year-1 and F = 1.17/year-1 for V. louti and M = 1.05/year-1 and F= 2.56/year-1 for V. albimarginata giving F/M ratios of 1.13:1 and 2.44:1. Beverton and Holt yield per recruit analysis gave exploitation rates (E = 0.53/year-1 and E = 0.71/year-1) exceeding the maximum sustainable value Emax = 0.37/year-1, indicating overexploitation of both species. To achieve the optimum exploitation rate of E50 = 0.24, fishing effort needs to be reduced by 29% for V. louti and 47% for V. albimarginata. Management options include setting a minimum legal size with recommended values of 32-33 cm and temporary closures during the peak reproductive season in May-June.